Methylglyoxal attenuates insulin signaling and downregulates the enzymes involved in cholesterol biosynthesis - Deshmukh, Arati B.; Bai, Shakuntala; Aarthy, T.; Kazi, Rubina S.; Banarjee, Reema; Rathore, Rajeshwari; Vijayakumar, M. V.; H. V. Thulasiram; Bhat, Manoj Kumar; Kulkarni, Mahesh J. (Molecular Biosystems, 2017)
Methylglyoxal (MG) is a highly reactive dicarbonyl known to be elevated under the hyperglycemic conditions of diabetes and is implicated in the development of diabetic complications. Therefore, the current study investigates the role of MG in exacerbating insulin resistance at the insulin signaling level, as well as its effect on the global proteomic level. By using insulin sensitive rat muscle cells (L6) and Chinese hamster ovary (CHO) cells stably expressing the insulin receptor (IR) and a glucose transporter fused with green fluorescent protein (GLUT4-GFP), we have observed that MG impairs insulin signaling, inhibits GLUT4 translocation and reduces glucose uptake. SWATH MS analysis, a label-free quantitative mass spectrometric approach, showed altered expression of 99 proteins out of 2404 identified in response to MG treatment. These proteins are mainly involved in stress response, protein folding and proteolysis. Some of the deregulated proteins such as thioredoxin 2, glutathione S transferase, T complex protein 1 subunit beta (tcbp1), heat shock protein 90 and E3 ubiquitin ligase were previously reported to be associated with either diabetes or insulin resistance. Interestingly, aminoguanidine (AMG), a potent dicarbonyl scavenger, restored the deleterious effects of MG. For the first time, we report that MG induces downregulation of enzymes involved in cholesterol biosynthesis such as acetyl-CoA acetyltransferase, hydroxymethylglutaryl-CoA synthase, farnesyl pyrophosphate synthetase, squalene monooxygenase, and lanosterol synthase. GC MS analysis for sterol metabolites corroborated the proteomic results; MG significantly reduced cholesterol production whereas AMG treatment restored cholesterol production to levels similar to the control. Thus, MG leads to primary defects in insulin signaling and cellular abnormalities at the proteomic and metabolic levels, both of which may contribute to the development of insulin resistance.

Mechanistic insights on anserine hydrolyzing activities of human carnosinases - Pandya, Vaibhav Kumar; Shankar, S. Shiva; Rajesh, S.; Rathore, Rajeshwari; Kumaran, Sangaralingam; Kulkarni, Mahesh J. (Biochemica ET Biophysica Acta- General Subjects, 2023)
Anserine and carnosine represent histidine-containing dipeptides that exert a pluripotent protective effect on human physiology. Anserine is known to protect against oxidative stress in diabetes and cardiovascular diseases. Human carnosinases (CN1 and CN2) are dipeptidases involved in the homeostasis of carnosine. In poikilothermic vertebrates, the anserinase enzyme is responsible for hydrolyzing anserine. However, there is no specific anserine hydrolyzing enzyme present in humans. In this study, we have systematically investigated the anserine hydrolyzing activity of human CN1 and CN2. A targeted multiple reaction monitoring (MRM) based approach was employed for studying the enzyme kinetics of CN1 and CN2 using carnosine and anserine as substrates. Surprisingly, both CN1 and CN2 can hydrolyze anserine effectively. The observed catalytic turnover rate (Vmax/[E]t) was 21.6 s-1 and 2.8 s-1 for CN1 and CN2, respectively. CN1 is almost eight-fold more efficient in hydrolyzing anserine compared to CN2, which is comparable to the efficiency of the carnosine hydrolyzing activity of CN2. The Michaelis constant (Km) value for CN1 (1.96 mM) is almost three-fold lower compared to CN2 (6.33 mM), representing higher substrate affinity for anserine-CN1 interactions. Molecular docking studies showed that anserine binds at the catalytic site of the carnosinases with an affinity similar to carnosine. Overall, the present study elucidated the inherent promiscuity of human carnosinases in hydrolyzing anserine using a sensitive LCMS/MS approach.
Keywords: Anserine; Carnosinase; Carnosine; Diabetes; LC-MS; MS; Multiple reaction monitoring (MRM); Promiscuity